The Effect of Job Stress and Corporate Culture on Turnover Intention Mediated By Employee Engagement (Empirical Study: Workers In The Field of Information Technology In Greater Jakarta) - Ahmad Danu Dwi Setiawan Wahidin; Andreas Heryjanto (Publikasi Indonesia, 2024)
This study aims to analyze the influence of job stress and corporate culture on turnover intention mediated by employee engagement among workers in the field of information technology in the Greater Jakarta area. The data was collected through a survey involving 310 respondents working in the information technology sector. The analysis method used in this study is Structural Equation Modeling (SEM) to evaluate the relationship between these variables. The results show that neither job stress nor corporate culture has effects on turnover intention. Job stress has no effects on employee engagement while corporate culture has significant positive effect on employee engagement. Employee engagement was found to play a significant role as a mediator in the relationship between corporate culture and turnover intention, while no mediation between corporate culture and turnover intention. These findings indicate the importance of corporate culture and the establishment of a supportive company through employee engagement to reduce the intention to leave the company.